The Pervasive Power of PowerPoint: How a Genre of Professional Communication Permeates Organizational Communication - Schoeneborn, Dennis (Organization studies, 2013)
This paper examines the pervasive role of Microsoft’s presentation software PowerPoint as a genre of professional and organizational communication. Frequently, PowerPoint is not only used for the primary function it was initially designed for, i.e., facilitating live presentations, but also for alternative purposes such as project documentation. Its application in a neighboring domain, however, poses a functional dilemma: does the PowerPoint genre preserve the features of its primary function, i.e., presentation, or rather adapt to the new function, i.e., documentation? By drawing on a communication-centered perspective, this paper examines PowerPoint’s role in the domain of project documentation as a clash between the constitutive affordances of professional and of organizational communication. To investigate this issue empirically, I conducted a case study at a multinational business consulting firm. The study allows identification of three distinct PowerPoint subgenres, which differ in how they adapt to the function of project documentation. This paper contributes to organization studies by specifying the boundary conditions under which a genre of professional communication such as PowerPoint can be expected to maintain its genre-inherent characteristics even in the face of contradictory organizational requirements and to impose these characteristics on a neighboring domain of organizational communication practices.